Comparison of Histopathological Features of Breast Cancer in Young and Elder Women - Amika Kour, Ikram Ullah Khan, Mohammad Sharif Sharifi, Matiullah Hamdard, Huma Zia, Pordil Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the major causes of mortality in females worldwide is breast cancer. It is evident from previous studies that breast cancer is significantly different clinicopathologically in young women than in older women. In contrast, other studies have found no such evidence. Objective: The current study's purpose was to compare breast cancer prevalence among young women to that in older patients regarding clinicopathological features and prognostic factors. Material and Methods: All the included patients with lesions in the breast were diagnosed via sonography/mammography and later subjected to histopathological biopsy. Who had undergone mastectomy or surgery for breast conservation, Adjuvant chemotherapy, tamoxifen, and radiation therapy as possible treatment choices. Tumour size, lymph node condition, histological grade, mitotic rate, oestrogen p53, the MIB-1 proliferation index, the prevalence of levels of estrogen receptors, c-erbB2 expression, and these components were analyzed using immunohistochemistry and histopathology. Prognostic comparisons were performed to those for women with this disease 60 years of age and older with a focus on it occurring or appearing again, Results: Clinical and pathological evaluations were performed on 40 patients with operable breast cancer under 40 and 80 patients older than 60 years. Elderly patients with breast cancer had a more aggressive phenotype than younger ones, with larger tumours (with 25 (31.25%) patients diagnosed with tumour size more than 5 cm), more lymph nodes involved, and greater levels of c-erbB2 (42 (52.5%) patients). However, these were typically only present in more advanced stages. Despite higher positive ER (34 (42.5%) patients) and PR (34 (42.5%) patients), additionally, a greater MIB-1 proliferation index (54 (67.5%) individuals) was observed in the elderly group compared to younger patients. Even though tamoxifen treatment and adjuvant chemotherapy became more popular. The rates of setback or re-appearing of the tumour, metastasis (30 (37.5%) individuals), and mortality (30 (37.50%) participants) were still more remarkable in elder patients. Conclusion: It is concluded that in Pakistan, the prognosis associated with breast cancer in young adults is poor. Keywords: p53, MIB Breast cancer, women – 40, fibroadenoma, papilloma